Measurement of motor conduction velocity with Hopf's technique in the diagnosis of mild peripheral neuropathies. Issue 2 (February 1981) - Rossi, B; Sartucci, F; Stefanini, A
Abstract : Hopf's technique was used to measure motor nerve conduction velocity of fibres in the deep peroneal nerve in clinical conditions where damage to the peripheral nervous system was probable. A particular distribution of motor nerve fibre conduction velocity was shown by the analysis of the findings in some of the groups investigated, illustrating the advantages of this method as compared with routine neurophysiological tests.